2013
DOI: 10.1158/0008-5472.can-11-3055
|View full text |Cite
|
Sign up to set email alerts
|

RhoB Differentially Controls Akt Function in Tumor Cells and Stromal Endothelial Cells during Breast Tumorigenesis

Abstract: Tumors are composed of cancer cells but also a larger number of diverse stromal cells in the tumor microenvironment. Stromal cells provide essential supports to tumor pathophysiology but the distinct characteristics of their signaling networks are not usually considered in developing drugs to target tumors. This oversight potentially confounds proof-of-concept studies and increases drug development risks. Here, we show in established murine and human models of breast cancer how differential regulation of Akt b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 40 publications
(51 reference statements)
3
41
1
Order By: Relevance
“…Consistent with this, RhoB deletion enhanced the frequency and reduced the latency of tumor formation in MMTV-PyMT mice (13). However, tumors that formed in RhoB knockout mice grew more slowly and had reduced angiogenesis.…”
Section: Rho Gtpase Function In Mouse Mammary Gland Tumorigenesis Andsupporting
confidence: 66%
See 1 more Smart Citation
“…Consistent with this, RhoB deletion enhanced the frequency and reduced the latency of tumor formation in MMTV-PyMT mice (13). However, tumors that formed in RhoB knockout mice grew more slowly and had reduced angiogenesis.…”
Section: Rho Gtpase Function In Mouse Mammary Gland Tumorigenesis Andsupporting
confidence: 66%
“…Thus, results of such studies must be interpreted with caution. Whole body deletion of RhoB or RhoC did not elicit large changes in mammary gland development, as these animals were able to nurse their young (12)(13)(14). Mammary gland-specific deletion of Rac1 also did not affect gland development during puberty or pregnancy (15).…”
Section: Rho Gtpases In Mammary Gland Developmentmentioning
confidence: 91%
“…Notably, it was reported that RhoB has a critical role in angiogenesis and controls stromal endothelial cells during breast tumorigenesis. 23,39 Among the transcriptional factors involved in mesenchymal migration, we observed that Slug, one of the most thoroughly investigated EMT regulators in lung cancer, 40 was strongly induced following RhoB loss. In parallel, E-cadherin, epithelial marker of EMT known to be downregulated notably by Slug, showed reduced levels of mRNA and protein.…”
Section: Discussionmentioning
confidence: 99%
“…Recently RhoB expression was reported to be increased in endothelial cells of the tumor stroma compared to adjacent normal tissue . Knockout experiments support a role for RhoB in tumor angiogenesis.…”
Section: Rho Gtpase Function In Tumor Angiogenesismentioning
confidence: 92%